ΕΧΩ ΤΗΝ ΚΑΥΧΗΣΙΝ: The Rhetorical Function of Paul's Boasting in Romans 15:17 - Kasih, Elia Mesrico Abdi (Theologia in Loco, 2023)
Paul’s boasting in Romans 15:17 raises the question of how the act of boasting needs to be perceived within the Christian world. Generally, boasting is considered a negative conduct and thus one should refrain from doing such action. However, this paper argues that Paul’s boasting in that verse has a positive significant rhetorical function that is correlated to gathering the support for his plan of mission to the worlds beyond Rome. In support of this argument, it is instructive to identify the different attitudes towards boasting both exhibited in the first-century Greco-Roman world and the Jewish tradition during that era. Moreover, classical rhetoric is also an important key to open the door to a clearer understanding of why in Romans 15:17 Paul boldly states that he has the pride or the reason to boast in Christ Jesus.